Proceedings of the 4th International Conference on Hardware/Software Codesign and System Synthesis 2006
DOI: 10.1145/1176254.1176293
|View full text |Cite
|
Sign up to set email alerts
|

Automatic selection of application-specific instruction-set extensions

Abstract: In this paper, we present a general and an efficient algorithm for automatic selection of new application-specific instructions under hardware resources constraints. The instruction selection is formulated as an ILP problem and efficient solvers can be used for finding the optimal solution. An important feature of our algorithm is that it is not restricted to basic-block level nor does it impose any limitation on the number of the newly added instructions or on the number of the inputs/outputs of these instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…As the name suggests, complete customization involves the whole instruction-set which is tuned towards the requirements of an application [2,3,4,5], while partial customization involves the extension of an existing instruction-set by means of a limited number of instructions [6,7,8,9,10,11,12,13,14]. In both cases the goal is to design an Instruction-Set containing the most important operations needed by the application to maximize the performance.…”
Section: Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…As the name suggests, complete customization involves the whole instruction-set which is tuned towards the requirements of an application [2,3,4,5], while partial customization involves the extension of an existing instruction-set by means of a limited number of instructions [6,7,8,9,10,11,12,13,14]. In both cases the goal is to design an Instruction-Set containing the most important operations needed by the application to maximize the performance.…”
Section: Motivationmentioning
confidence: 99%
“…A collection of templates constitutes a library of templates. Many authors assume the existence of templates which are given as an input and which are identified inside the subject graph [33,6,31], however this is not always the case and many authors develop their own templates [16,17,34,7,10,35,14,43,59].…”
Section: Instruction Generationmentioning
confidence: 99%
See 3 more Smart Citations